2015
DOI: 10.1103/physrevlett.115.025502
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Macroscopic Wear and Friction Laws on the Atomic Length Scale

Abstract: Using molecular dynamics, we simulate the abrasion process of an atomically rough Fe surface with multiple hard abrasive particles. By quantifying the nanoscopic wear depth in a time-resolved fashion, we show that Barwell's macroscopic wear law can be applied at the atomic scale. We find that in this multiasperity contact system, the Bowden-Tabor term, which describes the friction force as a function of the real nanoscopic contact area, can predict the kinetic friction even when wear is involved. From this the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 40 publications
4
39
2
Order By: Relevance
“…Modelling surfaces with realistic levels of roughness lubricated by a fluid is a case in point. Such a problem is still beyond the scales accessible to full MD simulation [269]. Alternatively, atomistic details of the surface topography and fluid close to 26 Friction | https://mc03.manuscriptcentral.com/friction the walls can be explicitly modelled and intimately linked to the macroscopic response of the fluid further from the walls.…”
Section: Linking MD To Larger Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling surfaces with realistic levels of roughness lubricated by a fluid is a case in point. Such a problem is still beyond the scales accessible to full MD simulation [269]. Alternatively, atomistic details of the surface topography and fluid close to 26 Friction | https://mc03.manuscriptcentral.com/friction the walls can be explicitly modelled and intimately linked to the macroscopic response of the fluid further from the walls.…”
Section: Linking MD To Larger Scalesmentioning
confidence: 99%
“…Eder et al [269] simulated the abrasion process of an atomically rough iron surface with multiple hard, abrasive particles. By monitoring the nanoscopic wear depth over time, the authors showed that the Barwell macroscopic wear law [270] holds even at the atomic scale.…”
Section: Nanoparticles As Dry Lubricantsmentioning
confidence: 99%
“…Equation (3) shows the formal Amontons' friction law, i.e., f = µ(L − L 0 ), where µ is the friction coefficient and L 0 is an offset. However, this result cannot show that Amontons' friction law is valid at the nanoscale for the nanopatterned surface because µ* is not independent of L 0 *, as explained by Eder et al [29] As shown in Figure 7c, the nanopatterned surface shows a high but finite friction force at L = 0 even at negative loads in adhesive contact, while a nearly no friction force at L = 0 is observed in nonadhesive contact. The friction force in adhesive contact is much greater than that in adhesive contact for the nanopatterned surface.…”
Section: Friction Lawmentioning
confidence: 64%
“…Our simulation data reveal that the friction force f depends linearly on the real contact area Areal for both the nanopatterned surface and the flat contact surface in either adhesive contact or in nonadhesive contact at the nanoscale. This linear real contact area dependence of the friction force has been found for H-terminated diamond surfaces [2] and atomically rough Fe surfaces [29] at the nanoscale. Figure 7b shows the average real contact area as a function of the normal load for the nanopatterned surface with l p = 2.17 nm and λ = 50%.…”
Section: Friction Lawmentioning
confidence: 82%
“…They became conscious of the rolling movement of sphere particle and found that the sliding of particle can prevent the large elastic recovery. Whilst, the friction and wear behaviors of diamond nanoparticles between other solid surfaces were studied via the MD method [26][27][28]. Eder et al observed a linear dependence of the contact area on the applied load in accordance with Greenwood-Williamson contact mechanics for the cubic abrasive particles on atomically rough iron surface [27].…”
Section: Introductionmentioning
confidence: 93%